Certificate‐based signature scheme in the standard model. (1st September 2017) - Zhou, Caixue; Cui, Zongmin
Abstract : Certificate‐based cryptosystem can eliminate the private key escrow problem inherent in the identity‐based cryptosystem and can simplify the costly certificate management in the traditional public key cryptosystem. In 2016, Lu et al . raised an open problem of whether the certificate‐based signature (CBS) scheme can be proved secure against the malicious‐but‐passive certifier attack. In this study, the authors try to solve this problem. They give an enhanced security model of the CBS scheme which can resist the malicious‐but‐passive certifier attack. Then they propose a concrete CBS scheme in the standard model by using bilinear pairings. They prove the scheme to be secure in the enhanced security model under the Squ‐CDH assumption. In this way, the authors give an affirmative answer to the above open problem. Finally, the authors evaluate the efficiency of the scheme which shows it to be practical. In addition, they find that malicious‐but‐passive certifier security cannot coexist with super adversary security in a CBS scheme in the standard model.